Price formation on the EuroMTS platform - Guglielmo Maria Caporale; Alessandro Girardi (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper examines the process of price discovery in the MTS system, which builds on the parallel quoting of euro-denominated government securities on a number of (relatively large) domestic markets and on a (relatively small) European marketplace (EuroMTS). Using twenty-seven months of daily data for 107 pairs of bonds, we present unambiguous evidence that trades on EuroMTS have a sizeable informational content.
Keywords: C32; G10; 330; MTS system; price discovery; Öffentliche Anleihe; Euromarkt; Börsenkurs; Effizienzmarktthese; Informationswert; Schätzung; EU-Staaten